PENGARUH BRAND IMAGE NOKIA TERHADAP PERILAKU KONSUMEN DENGAN KEPUASAN DAN LOYALITAS SEBAGAI VARIABEL INTERVENING PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS SEBELAS MARET SURAKARTA - Hendri Prasetyo (KREATIF : Jurnal Ilmiah Prodi Manajemen Universitas Pamulang, 2014)
This research is survey method. The target population in this study are consumer users in the Faculty of Economics Nokia UNS. Samples taken as 100. Sampling technique used was non-probability sampling with a purposive sampling method. Data analysis methods used in this study using linear regression test. Hypothesis testing is done by using the software SPSS for windows version 16. To determine the effect of variable - the variable to the satisfaction of brand image, brand image of loyalty, and brand image, satisfaction, loyalty to consumer behavior. For the t test demonstrate the value of 6.632 barand image affect satisfaction. brand image affects loyalty 4, 952. While the brand image, satisfaction, loyalty, influence consumer behavior Brand image calculated t value of 2.753 with a significant value of 0.07 <0.01, t value of 4.997 calculated consumer satisfaction with a significant value of 0.000 <0.05, t count value of Loyalty consumer at a significant value of 1.900 with 0.061 <0.1. F test indicates the value of 44.475. detriminasi coefficient (adjuted R Square) of 0.579, which means the variation of the three independent variables brand image, customer satisfaction, customer loyalty is able to explain 57.9% variation in the variable Y. So very good regression model, while the remaining 42.1% is explained by other factors. For further research on brand image can be considered to reproduce the respondents. Also consider other factors that may affect satisfaction, loyalty and consumer behavior. Keywords: Brand image, customer satisfaction, customer loyalty, consumer behavior.